The Gulf Familial Hypercholesterolemia Registry (Gulf FH): Design, Rationale and Preliminary Results - Al-Rasadi, Khalid; Alhabib, Khalid F.; Al-Allaf, Faisal; Al-Waili, Khalid; Al-Zakwani, Ibrahim; AlSarraf, Ahmad; Almahmeed, Wael; AlSayed, Nasreen; Alghamdi, Mohammad; Batais, Mohammed A.; Almigbal, Turky H.; Alnouri, Fahad; et al. (Current Vascular Pharmacology, 2020)
Aim: To determine the prevalence, genetic characteristics, current management and outcomes of familial hypercholesterolaemia (FH) in the Gulf region. Methods: Adult (18-70 years) FH patients were recruited from 9 hospitals and centres across 5 Arabian Gulf countries. The study was divided into 4 phases and included patients from 3 different categories. In phase 1, suspected FH patients (category 1) were collected according to the lipid profile and clinical data obtained through hospital record systems. In phase 2, patients from category 2 (patients with a previous clinical diagnosis of FH) and category 1 were stratified into definitive, probable and possible FH according to the Dutch Lipid Clinic Network criteria. In phase 3, 500 patients with definitive and probable FH from categories 1 and 2 will undergo genetic testing for 4 common FH genes. In phase 4, these 500 patients with another 100 patients from category 3 (patients with previous genetic diagnosis of FH) will be followed for 1 year to evaluate clinical management and cardiovascular outcomes. The Gulf FH cohort was screened from a total of 34,366 patients attending out-patient clinics. Results: The final Gulf FH cohort consisted of 3,317 patients (mean age: 47±12 years, 54% females). The number of patients with definitive FH is 203. In this initial phase of the study, the prevalence of (probable and definite) FH is 1/232. Conclusion: The prevalence of FH in the adult population of the Arabian Gulf region is high. The Gulf FH registry, a first-of-a-kind multi-national study in the Middle East region, will help in improving underdiagnosis and undertreatment of FH in the region.
Keywords: CHD